2016
DOI: 10.5371/hp.2016.28.1.35
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between the Fracture Types and the Complications after Internal Fixation of the Femoral Neck Fractures

Abstract: PurposeThis study aims to determine the correlation between the fracture patterns and the complications in patients with femoral neck fracture treated with internal fixation.Materials and MethodsThe study comprises 45 patients with femoral neck fracture treated with multiple screws or compression hip screw between May 2008 and April 2012. The mean age was 48 years at the time of the surgery and the mean duration from initial injury to surgery was 20 hours. The fracture patterns were identified according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Nonunion is the main complication following internal xation of the femoral neck fractures 18 . The 91% union rate in CMBP group is favorable comparable to the study for Pauwels type III fractures, in which union rates ranging from 73.7-89% 5,12,19,20 .…”
Section: Discussionsupporting
confidence: 69%
“…Nonunion is the main complication following internal xation of the femoral neck fractures 18 . The 91% union rate in CMBP group is favorable comparable to the study for Pauwels type III fractures, in which union rates ranging from 73.7-89% 5,12,19,20 .…”
Section: Discussionsupporting
confidence: 69%
“…Data on Garden classification were available for the systematic analysis from 14 studies [1620, 2224, 2630, 32]. The fixed effect model was chosen due to nonsignificant heterogeneity in intra-study comparisons ( I 2 = 1%, P = 0.44).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, a recent study that used a modified method to predict the outcome of femoral neck fractures demonstrated that a highly modified Pauwels angle was a risk factor for non-union [20]. Meanwhile, Jo et al described that the occurrences of non-union in the Pauwels type III fracture, subcapital-type fracture, and Garden stage III and IV fractures were higher than those of other types of femoral neck fracture with statistical significance [32]. Other previous literature found the same phenomenon with regard to the relationship between the Pauwels angle and non-union [14, 33–36].…”
Section: Main Textmentioning
confidence: 99%